Employment for Persons with Disabilities in Thailand: Opportunities and Challenges in the Labor Market - Cheausuwantavee, Tavee; Keeratiphanthawong, Sakulthip (Journal of Population and Social Studies [JPSS], 2021)
This mixed-methods study aimed to examine the current situation of the enforcement of laws for the employment of persons with disabilities (PWDs), and the difference in perspectives between PWDs and employers in Thailand. Results showed that there were only 8% of PWDs employed in competitive labor markets. The most relevant jobs from the employer’s perspectives for PWDs were unskilled labor. The majority of PWDs sought to be employed with essential support, including housing and transportation, in the mainstream open labor market. At the same time, employers were usually more concerned about particular approaches and accessible working environments for PWDs. Thus, this perspective gap was one reason for the low rate of employment of PWDs. In sum, there have been many challenges for the employment of PWDs in Thailand. Ways to improve career development for PWDs include the provision of suitable education and training, housing or dormitories located near workplaces, assistive technologies and reasonable accommodations in workplaces, and customized employment services for employed PWDs. Furthermore, positive attitudes, understanding, and collaboration between employers and PWDs should continuously be promoted.